1988
DOI: 10.1073/pnas.85.19.7134
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a Drosophila melanogaster guanine nucleotide regulatory protein beta-subunit gene and characterization of its expression during development.

Abstract: A Drosophila melanogaster gene encoding a protein with >80% sequence identity to the .3 subunits of mammalian guanine nucleotide-binding regulatory proteins (G proteins) has been cloned. The gene, which was mapped to 13F on the X chromosome by in situ hybridization, was cloned from a Drosophila genomic library by using a bovine transducin (20,21) prompted us to search for homologous genes in Drosophila melanogaster. We chose Drosophila, a metazoan organism amenable to genetic manipulation, to better understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…The D i c t y o s t e l i u r n G-protein f~-subunit shows a remarkable homology to the ~-subunits found in humans, D r o s o p h i l a , and C. e l e g a n s (Fong et al 1987;Gao et al 1987;Yarfitz et al 1988;van der Voorn et al 1990). Two common features of these homologous sequences have been noted previously, but the addition of the D i c t y os t e l i u r n sequence to the comparison markedly underscores these points.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The D i c t y o s t e l i u r n G-protein f~-subunit shows a remarkable homology to the ~-subunits found in humans, D r o s o p h i l a , and C. e l e g a n s (Fong et al 1987;Gao et al 1987;Yarfitz et al 1988;van der Voorn et al 1990). Two common features of these homologous sequences have been noted previously, but the addition of the D i c t y os t e l i u r n sequence to the comparison markedly underscores these points.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2, in which we have arranged the sequences according to the internal repeat structure described previously (Fong et al 1986), compares the Dictyostelium f3 to human [3-2 (Fong et al 1987;Gao et al 1987), C. elegans f3 (van der Voorn et al 1990), and Drosophila ~ {Yarfitz et al 1988). …”
Section: Isolation and Sequence Analysis Of The G-protein [3-subunit mentioning
confidence: 99%
“…The arcA product comprises seven repetitive segments with an insertion of nonrepetitive sequence spanning t20-amino acid residues between the sixth and the last repeat units. This well-conserved motif was discovered in subtypes of G# from human (13)(14)(15)(16)(17) and later in a divergent group of organisms (18)(19)(20)(21). Currently, this growing family of protein includes two proteins involved in RNA splicing, PRP4 (for precursor RNA processing) (30) and PRP17 (27); proteins critical to cell-cycle regulation, CDC4 (29) and CDC20 (30); a protein involved in regulating Ras function, MSI1 (31); a protein that functions as a mediator of glucose repression, TUP1 (32,33); a protein essential for the maintenance of killer double-stranded RNA, MAK1l (maintenance of killer) (30) in yeast; as well as C12.3 cDNA in chicken (26), Cblp (Chlamydomonas ,B subunit-like protein) (25), and Enhancer of split, the product of a Drosophila neurogenic locus (34).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the BY-2 cell line is particularly suitable for analyzing the cell cycle in plant cells. When we explored auxin-regulated genes upon auxin addition to tobacco BY-2 cells cultured without auxin for 3 days, we were able to isolate an auxin-regulated gene, which we designated arcA (for auxin-regulated gene from cultured cells).t Homology search in data bases revealed that arcA was homologous to genes that are structurally related to the ( subunit of heterotrimeric guanine nucleotide-binding regulatory proteins (G proteins) (13)(14)(15)(16)(17)(18)(19)(20)(21). In addition, we discuss the possibility that the arcA gene, as a member of the G protein ,B subunit (Gq) family, may have a role in inducing cell division.…”
mentioning
confidence: 99%
“…This missing protein is too large to be a G protein and its amino acid sequence does not resemble any known protein. The G protein of the fly eye, on the other hand, belongs to the G protein family (Blumenfeld et al, 1985;Bentrop and Paulsen, 1986;Paulsen and Bentrop, 1986;Devary et al, 1987;Yarfitz et al, 1988). The t~0 protein may be a component of a feedback loop which regulates the G protein activity or its interaction with the PLC.…”
Section: Discussionmentioning
confidence: 99%